Genetic and Non-Genetics Effect on Birth, Weaning, and Yearling Weight of Bali Cattle - A Gunawan; . Jakaria (Media Peternakan, 2011)
The aim of this study was to evaluate the effect of genetic and non-genetic factors on the growth traits including birth weight, weaning, and yearling weight of Bali cattle. Data were analyzed using generalized linear model (SAS) to observe non-genetic effect. To evaluate the genetic effect, the estimation of heritability were done using mixed models analysis with the dam and sire as random effect and sex, parity, year of birth, and season as fixed effect in the model besides the residual. The results showed that sex of calf had no significant influence on birth and weaning weight but had significant influence on yearling weight (P+0.07, 0.33+0.09, and 0.43+0.10 respectively. Heritability value of growth trait weaning and yearling weight in Bali cattle was quite moderate to high, so it was expected that selection in achieving increased gain on growth trait was effective.